Guidelines for producing statistics on violence against women : statistical surveys (United Nations publication sales no, 2014)
Violence against women is an obstacle to achieving the objectives of equality, development and peace. It violates the enjoyment by women of their human rights and fundamental freedoms. In all societies, women and girls are subjected to physical, sexual and psychological abuse that cuts across lines of income, class and culture. Data on the prevalence and incidence of various forms of violence against women, as well as the causes and consequences of violence, are the starting point for developing effective mechanisms at policy levels to eradicate this phenomenon. Properly designed and executed, surveys produce the most reliable data on the prevalence of violence and shed light on the scope, nature and consequences of many types of violence against women. Surveys can also collect information on circumstances surrounding violence, health consequences and the actions the women took to seek help.